Determinants of labor market outcome differentials between TVET and high school graduates - Benzon, Sean Kirstin Elomina (Animo Repository, 2022)
This study investigated the labor market differentials existing between Post-Secondary TVET graduates and High School graduates. This was done by investigating the direction and magnitude of a TVET degree’s effect on monthly wage and probability of employment through Naive Bayesian Regression and Propensity Score Matching; moreover, investigation of endogenous attributes to gauge what factors cause the differential, through Blinder-Oaxaca decomposition, was also performed. A sample from the STEP Skills Household Measurement 2015-2016 collected by the World Bank was utilized. The empirical methods unanimously agreed that TVET graduates earn a lower monthly wage than high school graduates; the result on employment likelihood was unanimous for Naive Bayesian Regression and Propensity Score Matching, which is that TVET graduates experience a higher probability of employment compared to high school graduates. However the Blinder-Oaxaca decomposition exhibited a converse result, such that high school graduates enjoy a higher employment probability compared to their TVET counterparts. The findings affirm the notion that a TVET degree does not necessarily result in improved labor market outcomes, and indicate that endogenous and exogenous factors are far more influential in securing improvements in wage and employment probability.